Say to the Sun, 'Don't Rise', and to the Moon, 'Don't Set', Two Oral Narratives from the Countryside of Maharashtra. Edited and translated by Anne Feldhaus with Ramdas Atkar and Rajaram Zagade. (1st August 2018) - Khangai, Ravi
Abstract : Say to the Sun, 'Don't Rise', and to the Moon, 'Don't Set', Two Oral Narratives from the Countryside of Maharashtra. Edited and translated by Anne Feldhaus with Ramdas Atkar and Rajaram Zagade. New York: Oxford University Press, 2014. xii +613 pp., $45.92. ISBN 978-0-199-35764-2 (hb).